Environment-friendly 3D printing mortar and preparation method thereof
By crushing and ball milling ALC solid waste with other materials, environmentally friendly 3D printing mortar with high density, mechanical strength and heat resistance are prepared, which solves the problem of ALC solid waste treatment and improves the construction speed of the mortar and durability.
Patent Information
- Application Number
- CN202411598908.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-03
AI Technical Summary
The problem of ALC solid waste disposal is becoming increasingly prominent, and it is necessary to develop an environmentally friendly 3D printing mortar and its preparation method to reuse these wastes.
The method of preparing environmentally friendly 3D printing mortar includes removing the steel bars of ALC solid waste, crushing it, grinding it into powder, mixing it with ordinary silicate cement, sulfoaluminate cement, quartz sand, expansion agent and fiber, and adding nanometers. Nano-reinforced materials such as grade silica form mortar with improved compactness, mechanical strength and heat resistance.
By reusing ALC solid waste, 3D printed mortar with improved compactness, mechanical strength and heat resistance are prepared, which solves the problem of ALC solid waste treatment and improves the construction speed and durability of the mortar.
Smart Images

Figure BDA0005127718680000051 
Figure BDA0005127718680000061
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of mortar materials, and in particular to an environmentally friendly 3D printing mortar and a preparation method thereof. Background Art
[0002] 3D printing technology is known as "the most iconic production tool of the third industrial revolution". In the construction industry, the combination of 3D printing technology and concrete materials marks an important attempt to transform the construction industry into an intelligent one. 3D printed concrete includes 3D printed mortar. Compared with traditional construction technology, 3D printed concrete has shown many advantages, such as: 1) Simplified construction process, no templates are required, saving economic, time and labor costs; 2) Refined construction operations, reducing errors and management pressure; 3) Integrated and automated construction, reducing labor demand and improving safety and civilization levels; 4) Accurate feeding, reducing resource loss and construction waste; 5) Personalized finished products, high-precision printing to meet the needs of different building structures.
[0003] With the rapid development of the autoclaved aerated lightweight concrete (ALC) industry, the problem of ALC solid waste disposal has become increasingly prominent. Specifically, ALC solid waste will be generated during the production and installation of ALC products, and a large amount of ALC solid waste will also be generated during the subsequent maintenance and demolition of ALC buildings. How to deal with these ALC solid wastes will become an urgent problem that needs to be solved.
[0004] In summary, it is necessary to develop an environmentally friendly 3D printing mortar and a preparation method thereof to reuse ALC solid waste and solve the problem of urgent treatment of ALC solid waste. Summary of the invention
[0005] The purpose of the present invention is to provide an environmentally friendly 3D printing mortar and a preparation method thereof. The specific technical scheme is as follows:
[0006] In a first aspect, the present invention provides a method for preparing an environmentally friendly 3D printing mortar, comprising:
[0007] Prepare dry powder and mixed solution separately;
[0008] The dry powder comprises the following raw material components: 250-400 parts of ordinary Portland cement, 30-250 parts of sulphoaluminate cement, 25-75 parts of ALC powder, 400-600 parts of quartz sand, 20-60 parts of expansion agent and 2-8 parts of fiber; the raw material components in the dry powder are mixed to prepare the dry powder; the ALC powder has a sieve residue of no more than 15% after passing through a 45 μm square hole sieve; the ALC powder is the powder obtained by removing steel bars from ALC solid waste;
[0009] The dry powder and the mixed liquid are mixed to obtain an environmentally friendly 3D printing mortar.
[0010] Optionally, the step of obtaining the ALC powder includes:
[0011] Step S1, crushing the ALC solid waste to form first crushed materials;
[0012] Step S2, removing steel bar fragments from the first scraps by magnetic separation;
[0013] Step S3, crushing the first crushed material after magnetic separation again to form second crushed material;
[0014] Step S4: ball-milling the second crushed material to obtain the ALC powder.
[0015] Optionally, the quartz sand particles are 40-70 meshes and the mud content is not more than 0.5%.
[0016] Optionally, the expansion agent includes calcium sulphoaluminate.
[0017] Optionally, the fiber includes basalt fiber; the basalt fiber has a single filament diameter of 15-18 μm, a fiber length of 3-9 mm, and a density of 2.8-3.3 g / cm3.
[0018] Optionally, the strength grade of the ordinary Portland cement is 42.5-52.5 MPa; the strength grade of the sulphoaluminate cement is 42.5-52.5 MPa;
[0019] Optionally, the mixed liquid includes the following raw material components: 5-20 parts of nano-reinforcement material, 1-3 parts of hydroxypropyl methylcellulose ether, 0.5-5 parts of water reducer, 0.5-5 parts of defoamer and 50-150 parts of water; the raw material components in the mixed liquid are mixed to prepare the mixed liquid; the nano-reinforcement material includes nano-scale silicon dioxide.
[0020] Optionally, the water reducer includes a polycarboxylate water reducer; the water reduction rate of the polycarboxylate water reducer is not less than 25%; and the defoamer includes a polyether defoamer.
[0021] Optionally, the stirring rate used when mixing to prepare the dry powder is 200-240r / min; the stirring rate used when mixing to prepare the mixed liquid is 200-240r / min; the stirring rate used when mixing to prepare the environmentally friendly 3D printing mortar is 200-240r / min.
[0022] In a second aspect, the present invention provides an environmentally friendly 3D printing mortar, which is prepared using the method for preparing the environmentally friendly 3D printing mortar.
[0023] The application of the technical solution of the present invention has at least the following beneficial effects:
[0024] (1) The present invention provides a method for preparing an environmentally friendly 3D printing mortar, which can not only recycle ALC solid waste and solve the problem of ALC solid waste that needs to be dealt with urgently, but also prepare 3D printing mortar materials with improved density, mechanical strength and heat resistance. Specifically, the ALC powder used in the dry powder raw material is the powder after the steel bars are removed from the ALC solid waste, thereby realizing the recycling of the ALC solid waste; the ALC powder contains the following hydration products: tobermorite, calcium silicate stone, orthorhombic spar and hydrated calcium silicate, and these hydration products all have a dense microstructure, so that after the ALC powder is added to the environmentally friendly 3D printing mortar, it helps to fill the pores in the mortar material, improve the microstructure of the mortar, improve the density and mechanical strength of the mortar, and increase durability; at the same time, the tobermorite in the hydration product is resistant to high temperatures of up to 50 0℃, hard calcium silicate stone can remain stable at high temperatures of 800-1000℃, orthorhombic spar can even maintain structural stability at high temperatures above 1000℃, and hydrated calcium silicate can maintain structural stability at high temperatures above 300℃. Therefore, the addition of ALC powder can also improve the heat resistance of mortar materials; in addition, the residue of ALC powder after sieving through a 45μm square hole sieve is no more than 15%, which makes the ALC powder particles small and uniform, and it is easier to fill the tiny gaps in the mortar, making the microstructure of the mortar more uniform and the compactness better, further improving the mechanical strength and increasing durability.
[0025] (2) The present invention also uses nano-scale silicon dioxide in the preparation method of environmentally friendly 3D printing mortar, which can not only accelerate the cement hydration reaction, shorten the setting time, and increase the construction speed, but also improve the mechanical properties and durability of the mortar. Specifically, nano-scale silicon dioxide can react with calcium hydroxide produced by the hydration of ordinary silicate cement to generate calcium silicate gel, accelerate the cement hydration reaction, shorten the setting time, and increase the construction speed; in addition, the nano-scale silicon dioxide particles are small and uniform, and it is easier to fill the tiny gaps in the mortar, making the mortar more compact, further improving the mechanical strength, and increasing the durability. DETAILED DESCRIPTION
[0026] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.
[0027] Embodiment 1:
[0028] A method for preparing an environmentally friendly 3D printing mortar, comprising:
[0029] Prepare dry powder and mixed solution separately;
[0030] The dry powder comprises the following raw material components: 360 parts of ordinary Portland cement, 40 parts of sulphoaluminate cement, 30 parts of ALC powder, 500 parts of quartz sand, 40 parts of expansion agent and 3 parts of fiber; the raw material components in the dry powder are mixed to prepare the dry powder; the stirring rate used when mixing to prepare the dry powder is 200r / min; the ALC powder has a sieve residue of no more than 15% after passing through a 45μm square hole sieve; the ALC powder is the powder after removing steel bars from ALC solid waste;
[0031] The mixed liquid comprises the following raw material components: 5 parts of nano-enhanced material, 2 parts of hydroxypropyl methylcellulose ether (viscosity is 200,000), 1 part of water reducer, 1 part of defoamer and 120 parts of water; the raw material components in the mixed liquid are mixed to prepare the mixed liquid; the stirring rate used when mixing to prepare the mixed liquid is 200r / min; the nano-enhanced material is nano-grade silicon dioxide.
[0032] The dry powder and the mixed liquid are mixed to obtain an environmentally friendly 3D printing mortar; the stirring rate used when mixing to prepare the environmentally friendly 3D printing mortar is 200 r / min, and the stirring time is 3 min.
[0033] The steps of obtaining the ALC powder include:
[0034] Step S1, the ALC solid waste is initially crushed by a shredder to form first crushed materials;
[0035] Step S2, removing steel bar fragments from the first scraps by magnetic separation;
[0036] Step S3, crushing the first crushed material after magnetic separation again to form second crushed material;
[0037] Step S4, grinding the second crushed material by a ball mill to obtain the ALC powder.
[0038] The quartz sand particles are 40-70 meshes and have a mud content of no more than 0.5%. In this embodiment 1, the mud content of the quartz sand particles is 0.2%.
[0039] The expansion agent is calcium sulphoaluminate.
[0040] The fiber includes basalt fiber; the monofilament diameter of the basalt fiber is 15-18 μm, the fiber length is 3-9 mm, and the density is 2.8-3.3 g / cm 3, tensile strength is 4100MPa, and elastic modulus is 100GPa. Considering the small size of basalt fiber products, it is difficult for manufacturers to produce basalt fiber products of fixed size. Therefore, the size of the basalt fiber product provided in Example 1 fluctuates, but its corresponding tensile strength and elastic modulus can reach a fixed value level.
[0041] The strength grade of the ordinary Portland cement is 42.5 MPa; the strength grade of the sulphoaluminate cement is 42.5 MPa.
[0042] The water reducer is a polycarboxylate water reducer; the water reduction rate of the polycarboxylate water reducer is not less than 25%, and the water reduction rate of the polycarboxylate water reducer in this embodiment 1 is 26.8%; the defoamer is a polyether defoamer.
[0043] Embodiment 2:
[0044] The difference from Example 1 is that the amount of ALC powder is increased to 45 parts.
[0045] Embodiment 3:
[0046] The difference from Example 1 is that the amount of ALC powder is increased to 60 parts.
[0047] Embodiment 4:
[0048] The difference from Example 3 is that the amount of nano-reinforcement material is increased to 10 parts.
[0049] Embodiment 5:
[0050] The difference from Example 3 is that the amount of nano-reinforcement material is increased to 15 parts.
[0051] Embodiment 6:
[0052] The difference from Example 5 is that the amount of ordinary Portland cement is reduced to 320 parts, and the amount of sulphoaluminate cement is increased to 80 parts.
[0053] Embodiment 7:
[0054] The difference from Example 5 is that the amount of ordinary Portland cement is reduced to 280 parts, and the amount of sulphoaluminate cement is increased to 120 parts.
[0055] Comparative Example 1:
[0056] Different from Example 1, no nano-reinforcement material is used.
[0057] Comparative Example 2:
[0058] Different from Example 2, no nano-reinforcement material is used.
[0059] Comparative Example 3:
[0060] Different from Example 3, no nano-reinforcement material is used.
[0061] Comparative Example 4:
[0062] Different from Example 6, no nano-reinforcement material is used.
[0063] Comparative Example 5:
[0064] Different from Example 7, no nano-reinforcement material is used.
[0065] Except for ALC powder, all raw materials used in Examples 1-7 and Comparative Examples 1-5 are commercially available raw materials. The environmentally friendly 3D printing mortars prepared in Examples 1-7 and Comparative Examples 1-5 were subjected to setting time test and 28d (d is day) mortar strength test, respectively. The test results are shown in Table 1. The test method is GB / T 17671-2021 "Test method for strength of cement mortar (ISO method)", and the test equipment is DYE-300 fully automatic flexural and compression integrated machine.
[0066] Table 1 Setting time and 28d mortar strength test results
[0067]
[0068]
[0069] From the data in Table 1, it can be seen that in Examples 1-3, with the increase in the amount of ALC powder, the initial setting time and the final setting time both show a shortening trend, and the 28d mortar strength data show an increasing trend. This is because within the range of ALC powder dosage, with the increase in the amount of ALC powder, the mortar density is better, the contact opportunity between the mortar particles increases, and the hydration reaction is accelerated, thereby showing a trend of shortening the initial setting time and the final setting time; with the increase in the amount of ALC powder, the mortar density is better, which is conducive to improving the mortar strength, and then the 28d mortar strength data shows an increasing trend.
[0070] Compared with Comparative Examples 1-3, the nano-scale silica used in Examples 1-3 of the present invention can not only shorten the setting time, increase the construction speed, but also improve the 28d mortar strength performance. Similarly, compared with Comparative Examples 4-5, the nano-scale silica used in Examples 6-7 of the present invention can not only shorten the setting time, increase the construction speed, but also improve the 28d mortar strength performance. This is because the nano-scale silica used in the present invention can react with the calcium hydroxide produced by the hydration of ordinary silicate cement to generate calcium silicate gel, accelerate the cement hydration reaction, shorten the setting time, and increase the construction speed; in addition, the nano-scale silica particles are small and uniform, and it is easier to fill the tiny gaps in the mortar, so that the compactness of the mortar is better, and the mechanical strength is further improved, thereby improving the 28d mortar strength performance.
[0071] Compared with Comparative Example 3, the dosage of nano-silicon dioxide in Examples 3-5 of the present invention increases successively, the initial setting time and the final setting time both show a shortening trend, and the 28d mortar strength data show an increasing trend.
[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing an environmentally friendly 3D printing mortar, characterized in that: include: Prepare dry powder and mixed solution separately; The dry powder comprises the following raw material components: 250-400 parts of ordinary Portland cement, 30-250 parts of sulphoaluminate cement, 25-75 parts of ALC powder, 400-600 parts of quartz sand, 20-60 parts of expansion agent and 2-8 parts of fiber; the raw material components in the dry powder are mixed to prepare the dry powder; the ALC powder has a sieve residue of no more than 15% after passing through a 45 μm square hole sieve; the ALC powder is the powder obtained by removing steel bars from ALC solid waste; The dry powder and the mixed liquid are mixed to obtain an environmentally friendly 3D printing mortar.
2. The method for preparing the environmentally friendly 3D printing mortar according to claim 1, characterized in that: The steps of obtaining the ALC powder include: Step S1, crushing the ALC solid waste to form first crushed materials; Step S2, removing steel bar fragments from the first scraps by magnetic separation; Step S3, crushing the first crushed material after magnetic separation again to form second crushed material; Step S4, ball-milling the second crushed material to obtain the ALC powder.
3. The method for preparing the environmentally friendly 3D printing mortar according to claim 1, characterized in that: The quartz sand particles are 40-70 meshes and the mud content is no more than 0.5%.
4. The method for preparing the environmentally friendly 3D printing mortar according to claim 1, characterized in that: The expansion agent includes calcium sulphoaluminate.
5. The method for preparing the environmentally friendly 3D printing mortar according to claim 1, characterized in that: The fiber includes basalt fiber; the monofilament diameter of the basalt fiber is 15-18 μm, the fiber length is 3-9 mm, and the density is 2.8-3.3 g / cm 3 .
6. The method for preparing the environmentally friendly 3D printing mortar according to claim 1, characterized in that: The strength grade of the ordinary Portland cement is 42.5-52.5 MPa; the strength grade of the sulphoaluminate cement is 42.5-52.5 MPa.
7. The method for preparing the environmentally friendly 3D printing mortar according to any one of claims 1 to 6, characterized in that: The mixed liquid comprises the following raw material components: 5-20 parts of nano-enhanced material, 1-3 parts of hydroxypropyl methylcellulose ether, 0.5-5 parts of water reducer, 0.5-5 parts of defoamer and 50-150 parts of water; the raw material components in the mixed liquid are mixed to prepare the mixed liquid; the nano-enhanced material comprises nano-grade silicon dioxide.
8. The method for preparing the environmentally friendly 3D printing mortar according to claim 7, characterized in that: The water reducing agent includes a polycarboxylate water reducing agent; the water reducing rate of the polycarboxylate water reducing agent is not less than 25%; and the defoaming agent includes a polyether defoaming agent.
9. The method for preparing the environmentally friendly 3D printing mortar according to claim 7, characterized in that: The stirring rate used when mixing to prepare the dry powder is 200-240r / min; the stirring rate used when mixing to prepare the mixed liquid is 200-240r / min; the stirring rate used when mixing to prepare the environmentally friendly 3D printing mortar is 200-240r / min.
10. An environmentally friendly 3D printing mortar, characterized in that: The environmentally friendly 3D printing mortar is prepared by the preparation method of claim 7.